Fiscal Strategy for Local Food Resilience: Empirical Evidence from East Java 2018-2024 - Satya Laksana; Muthmainnah Ruslan (Pusbindiklatren Bappenas, 2025)
This research examines the influence of fiscal capacity and regional spending on food security across 38 regencies/cities in East Java from 2018 to 2024. Capital expenditures in the economy, health, education, and housing sectors are analyzed as these functions shape key determinants of food resilience. Using panel data with fixed effects and mean group estimators, the study evaluates both contemporaneous and lagged effects on the Regional Food Security Index (IKPD). Results show that fiscal capacity and health-sector capital expenditure consistently strengthened food security, indicating the central role of health infrastructure and personnel. In contrast, spending on the economic, education, and housing sectors showed inconsistent impacts, suggesting limited targeting of food-related outcomes. Structural factors—such as access to clean water, women’s education, and the availability of health personnel—also significantly shaped IKPD performance. These findings highlight the need for adaptive, evidence-based fiscal policies tailored to local contexts to guide the 2025–2029 mid-term regional development planning.